2009
DOI: 10.1111/j.1600-0765.2008.01153.x
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette smoke extract modulates human β‐defensin‐2 and interleukin‐8 expression in human gingival epithelial cells

Abstract: Human gingival epithelial cells play a critical role in orchestrating the innate immune responses of periodontal tissue via TLR signalling. Our results represent the first demonstration that CSE can modulate HGEC function by suppressing hBD-2 and enhancing IL-8 production, and this may be, in part, a possible mechanism which promotes periodontal disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
77
2
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(89 citation statements)
references
References 38 publications
4
77
2
4
Order By: Relevance
“…Correspondingly, the activated immune response limits innate response and, hence, secretion of β-defensins (42) . Our findings were in agreement with previous studies shown that smoking downregulates hβD-2 expression (37,39,43) .…”
Section: According To Fan Et Al (2015)supporting
confidence: 94%
See 1 more Smart Citation
“…Correspondingly, the activated immune response limits innate response and, hence, secretion of β-defensins (42) . Our findings were in agreement with previous studies shown that smoking downregulates hβD-2 expression (37,39,43) .…”
Section: According To Fan Et Al (2015)supporting
confidence: 94%
“…At three months greater mean hβD-2 level was recorded in non-smokers group, with no statistically significant difference. At baseline, the low level of hβD-2 in smoker's group could be explained by the fact that periodontopathogenic microorganisms mainly P.gingivalis, which had a specific role in β-defensins degradation was found in smokers more than in non-smokers (39,40) . Moreover, bacteria with resistance to β-defensins, such as T. denticola and P.gingivalis, survive and colonize on epithelial surfaces, and eventually, invade gingival tissues (41) .…”
Section: According To Fan Et Al (2015)mentioning
confidence: 94%
“…It is therefore possible that vanadium contributed to the inhibition of HBD-2 production in response to M. tuberculosis. Interestingly, exposure of gingival epithelial and normal human bronchial epithelial cells to cigarette smoke, which also contains vanadium, similarly reduces HBD-2 mRNA expression and peptide production in vitro in response to LPS from Pseudomonas aeruginosa (51). It has been proposed that the downregulation of HBD-2 in P. aeruginosainfected cells by cigarette smoke may be due to the downregulation of fatty acid-binding protein 5 (FABP5).…”
Section: Discussionmentioning
confidence: 99%
“…Antimicrobial peptides are important effector molecules of the lung innate immune system, and BDs, especially BD-2, are the principal family of antimicrobial peptides in respiratory tract, which are mainly produced by airway epithelial cells [1]. Several studies have recently demonstrated a suppressive effect of CS on hBD-2 expression by cultured human sinonasal, gingival and airway epithelial cells in vitro and decreased hBD-2 levels in pharyngeal washing fluid and sputum from smokers with acute pneumonia in vivo [9][10][11], indicating that CS exposure possibly inhibits airway epithelial hBD-2 production, which links cigarette smoking with increased susceptibility of respiratory tract to microbial infections. However, SHIBATA et al [12] reported upregulated mBD-2 mRNA expression in lung tissues after 6-month CS exposure, and we have further demonstrated, in the present study, that 4-week repeated CS exposure stimulated rBD-2 mRNA and protein expression in rat airways.…”
Section: Discussionmentioning
confidence: 99%
“…However, little is known about the effect of CS on BD-2 expression. Very recently, LEE et al [9] and MAHANONDA et al [10] reported that acrolein (a major component of cigarette smoke) and cigarette smoke extract, suppressed hBD-2 expression by sinonasal epithelial cells and gingival epithelial cells. Results from a study by HERR et al [11] showed decreased levels of hBD-2 in pharyngeal washing fluid and sputum from current and former smokers with acute pneumonia compared with that from never smokers, and demonstrated that smoke exposure reduced in vitro hBD-2 expression in airway epithelium in response to bacterial stimulation.…”
mentioning
confidence: 99%